Two new species and three new provincial records of Neoperla (Plecoptera: Perlidae) from Nanling Mountains, China - Mo, Raorao; Wang, Ying; Wang, Guoquan; Li, Weihai; Murányi, Dávid (Zootaxa, 2021)
Two species of the genus Neoperla (Plecoptera: Perlidae) are described as new: Neoperla annulatispina Mo, Li & Wang, sp. nov. from Guangdong and Neoperla similidelphina Mo, Li & Murányi, sp. nov. from Guangxi. Distinctness of Neoperla annulatispina from morphologically similar Neoperla nigromarginata Li & Zhang, 2014 was confirmed by comparing COI barcode sequences. Three additional Neoperla species are presented as new provincial records from the Nanling Mountains are given: Neoperla chebalinga Chen & Du, 2016, Neoperla leigongshana Du & Wang, 2007 and Neoperla maolanensis Yang & Yang, 1993. Illustrations and color photographs are provided for each species, and the new species are compared to similar taxa. Distributions of Neoperla species recorded in the present study are also presented.